2009
DOI: 10.1177/0898264309351310
|View full text |Cite
|
Sign up to set email alerts
|

Volunteering and Trajectories of Depression

Abstract: Overall findings highlight the importance of assessing the long-term health impact of volunteering and doing so under diverse social structural contexts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 35 publications
(45 reference statements)
2
63
2
1
Order By: Relevance
“…The results also demonstrated that the CSES could discriminate between the groups; that is, the scores of all the CSES factors and sub-scales in the CVOL group were higher than those in the GEN group (Table 4). This finding is also consistent with outcomes that volunteers have advantages over other citizens in terms of physical activity [42], mental health [43], self-rated health [44], and general self-efficacy [31]. …”
Section: Discussionsupporting
confidence: 85%
“…The results also demonstrated that the CSES could discriminate between the groups; that is, the scores of all the CSES factors and sub-scales in the CVOL group were higher than those in the GEN group (Table 4). This finding is also consistent with outcomes that volunteers have advantages over other citizens in terms of physical activity [42], mental health [43], self-rated health [44], and general self-efficacy [31]. …”
Section: Discussionsupporting
confidence: 85%
“…Research has found that participation in voluntary services is significantly predictive of better mental and physical health [1, 2], life satisfaction [3], self-esteem [3, 4], happiness [5, 6], lower depressive symptoms [4, 7], psychological distress [3, 8], and mortality and functional inability [8, 9]. As proved recently, the health benefits of volunteering are not due to self-selection bias.…”
Section: Introductionmentioning
confidence: 99%
“…What remains uncharted for the relationship between volunteering and health outcomes is pertinent to whether volunteering may have cumulative effects on health and what form of volunteering is preferable for promoting health benefits for volunteers [1, 7, 9]. Regarding the volunteering and health connection, the role accumulation perspective supports the position that a volunteer who concomitantly participates in different types of voluntary services can benefit his or her health most [2, 4, 5, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Although prior work has examined differing mental well-being selection and causation processes due to life-course factors such as age or social integration (Kim and Pai 2010;Li and Ferraro 2006;Omoto et al 2010;Piliavin and Siegl 2007), other resources remain overlooked. Because education is one of the strongest human resources or capitals for volunteering (Wilson 2012), mental health may more effectively lead to volunteering given higher levels of education.…”
Section: Introductionmentioning
confidence: 99%